Academic Capability Under the Lens: Analyzing the Comprehensive Exam Program - Rohiat, Salastri; Nahadi; Sriyati, Siti (Chemistry Education Department, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga, 2025)
This program evaluation is intended to describe the results of the comprehensive examination program for prospective teachers in all science fields. The results of this program evaluation are expected to make a specific contribution to the sustainability of the comprehensive examination program being held and are expected to contribute to education in general. This program evaluation uses the CIPP (Context, Input, Process and Product) evaluation model. Data sources for this program evaluation consist of documents and human resources. Based on the results of a thorough evaluation of the comprehensive examination program, it can be concluded that recommendations to improve the effectiveness and sustainability of this program are very important. Evaluations covering context, input, process and product aspects show that there are several areas that need to be improved and improved. An effective and sustainable comprehensive examination program is not only an evaluation tool, but also an integral part of their academic and professional career development. With a holistic and sustainable approach, study programs can ensure that comprehensive exams provide maximum benefits for students and educational institutions as a whole.